Frequency Scale for the Symptoms of GERD Score for Gastroesophageal Reflux Disease in Koja Hospital - Suzanna Ndraha (The Indonesian Society for Digestive Endoscopy, 2010)
Background: The frequency scale for the symptoms of GERD (FSSG) was a specific questionnaire to gastroesophageal reflux disease (GERD), which has been validated against the endoscopic findings in Japan. The high score FSSG is one of the factors related to failure of proton pump inhibitor (PPI) mono therapy. The purpose of this study is to determine FSSG score in patients with GERD at Koja hospital, in order to predict the need for combination therapy of PPI with pro- kinetic drug or PPI only. Method: Dyspeptic patients which had have heartburn and/or regurgitation were collected in the period of March until July 2010. The FSSG score was obtain containing 12 questions which consisted of seven questions for reflux symptoms and five questions for dysmotility/dyspeptic symptoms. Results: There were 129 patients, 51 (39.5%) males and 78 (60.5%) females, mostly in the age group of 40 years (55.8%), body mass index of most patients (66.6%) were normal, only 12.4% were overweight. FSSG score revealed the mean of total score of 17.6 ± 6.9. From 129 dyspepsia patients who complained heartburn and or regurgitation, obtained 121 (94%) met criteria for GERD with cutoff eight. The mean of reflux score was 7.4 ± 4.6 while the mean of dyspeptic/dysmotility score was 10.1 ± 4. Thus from 129 patients studied, the symptoms of dyspeptic/dysmotility more dominant than symptoms of reflux Conclusion: GERD patients in Koja hospital have a high mean FSSG score, whereas dysmotility symptoms was proved to be more dominant than acid reflux Keywords: GERD, FSSG, dyspeptic/dysmotility score, reflux score